FRI0167 Anti-TNF do not modify the interferon signature in patients with rheumatoid arthritis and lupus ("rhupus"). (23rd January 2014) - Sparsa, L.; Sordet, C.; Alsaleh, G.; Ardizzone, M.; Javier, R.M.; Kleinman, J.F.; Gottenberg, J.E.; Sibilia, J.
Abstract : Background: We recently reported the clinical efficacy and safety of anti-TNF-alpha in a cohort of 15 rhupus patients with rheumatoid arthris and systemic lupus ("rhupus"). TNF-alpha and type I interferon (IFN) were reported to be crossregulated in a gene expression study of patients with juvenile idiopathic arthritis. Treating with anti-TNF these patients could raise the concern of a potential overexpression of IFN-inducible genes and chemokines, which play a pathogenic role in SLE. Objectives: To evaluate changes in levels of IFN-inducible genes and chemokines under treatment with anti-TNF for RA associated with SLE. Methods: Among the 15 patients with RA and SLE, PBMCs and serum were collected before and after anti-TNF initiation (median: 8 months) in 6 patients. Total RNA was extracted from PBMC using the Nucleospin RNA II extraction kit according to the manufacturer's instructions and reverse transcribed using the First Strand cDNA Synthesis Kit according to the manufacturer's instructions (In Vitrogen). Real-time quantitative RT-PCR was performed in a total volume of 20 μl using SensiMix Plus SYBR kit (Quantace, Corbett Life Science)and gene specific primers for BAFF, IFTIMMX-1, PKR. Serum CXCL10, CCL2 and CCL19 levels were assessed using R&D ELISA. Results: All 15 patients were women with a mean age of 51 years [20-75]. The mean duration of treatment was 34.7 and 33.7 (4-69) months with etanercept and adalimumab, respectively. 8.3 infections for 100 patient years occurred. No mycobacteria infection, no lymphoproliferation and no cancer were observed. Also, no cutaneous, renal or other systemic flare of SLE occurred. No death was observed. After 2 years of follow-up, the mean decrease of DAS 28 and SLEDAI was -3 [-0.75 to -4.89] -5.13 [0 – 6], respectively. Corticosteroid dosage significantly decreased from 10mg/d to 5mg/d. No statistical significant increase in gene expressions of 4 different IFN-inducible genes, BAFF (2.2 to 0 fold), MX1 (17.2 to 0 fold), IFITM (1.2 to 0 fold), and PKR (19.3 to 0 fold) Likewise, no significant change was observed in serum levels of 3 IFN-inducibles chemokines: CXCL10 (82 to 56.2 pg/ml, p=0.87), CCL2 (343.8 to 729.4 pg/ml, p=0.375) and CCL19 (316.3 to 335.9 pg/ml, p=0.875). Conclusions: This study shows good short term tolerance and efficacy of anti-TNF in patients with SLE and RA ("rhupus"). The absence of increase in IFN-inducible genes and chemokines, which are validated prognostic markers of disease activity in SLE, might contribute to the absence of SLE flares observed in rhupus patients treated with anti-TNF. Disclosure of Interest: None Declared